Effect of nitrogen level and time of application on growth, seed yield and oil content of Sunflower (Helianthus annuus L.), Gezira State, Sudan - A. A. Hammadi, Abdulluh; Daffalla, Ahmed E.; Mohamed, Ibrahim E. (Gezira Journal of Agricultural Science; Vol 19 No 2 (2021), 2023)
Nitrogen (N) is one of the major nutrients that enhances the metabolic processes that leads to increase in growth and yield of crops. However, the time of nitrogen application affects seed yield of sunflower and reduces nitrogen losses. The objective of the current study was to investigate the effects of nitrogen level and time of application on growth, seed yield and oil content (%) of sunflower. Field trials were carried out at the experimental farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, during  summer and winter  seasons of 2017/18. Four  nitrogen levels (0, 43, 86, 129 Kg N/ha))  and three times of nitrogen application, namely, at early + at budding, at early + at flowering and at budding + at flowering were used. ( A randomized complete block design with three replicates was used). The sunflower cultivar Hysun-33 was used. Results indicated that nitrogen had significant effects on plant height, LAI, dry weights, number of seeds/plant,  1000 seed weight, empty seeds percentage (%), seed yield and oil content (%) in both seasons. Time of N application had significant  effects on plant height, dry weights, number of seeds/plant and oil content (%) in both seasons and on 1000  seed weight and seed yield in summer season only. The highest seed yield (2852.4kg/ha) was obtained when 86 kg N /ha was applied at early + at flowering in summer season and (2373.6 kg/ha) when 129 kg/ha was applied at budding + at flowering in winter season.  However,  zero nitrogen application obtained significantly highest oil content in summer season, while 129kg N ̸ ha  at budding +at flowering in winter season. It is recommended to apply 86 or 129 kg N /ha at early +at flowering or at budding + flowering in summer and winter seasons, respectively. However, to achieve the highest  oil content,  nitrogen application is not advisable  under Gezira conditions, تأثير مستوى النتروجين وموعد التطبيق على نمو وإنتاجية البذور ونسبة زيت زهرة الشمس، ولاية الجزيرة، السودان --------- 1                    عبد الله عبد الستار عبد الله حمادي، 2 احمد الطيب دفع الله و 2 إبراهيم البشير محمد                    1  كلية الزراعة، جامعة الانبار، بغداد ، العراق.          2 كلية العلوم الزراعية، جامعة الجزيرة، ود مدني، السودان.   الخلاصــــــة         يعتبر  النتروجين من العناصر الغذائية الكبرى التي تسهم في نمو جيد وإنتاجية عالية للمحصول من خلال إسهامه في عمليات البناء الحيوي للنبات. كما أن مواعيد إضافة النتروجين لزهرة الشمس يقلل من ضياع السماد  المضاف وبالتالي زيادة الانتاجية.  تهدف هذه الدراسة إلى تحديد الجرعة المناسبة والوقت الأمثل لإضافتها لتحقق أعلى إنتاجية ونسبة زيت لزهرة الشمس. أجريت التجربة الحقلية في المزرعة التجريبية لكلية العلوم الزراعية، جامعة الجزيرة، ود مدني، السودان خلال صيف وشتاء  2017/2018م. تم استخدام نظام القطاعات العشوائية الكاملة بثلاث مكررات. اشتملت الدراسة على أربعة مستويات من النتروجين )0، 43 ، 86 و 129كجم نتروجين /هكتار(، وثلاثة مواعيد لإضافة السماد: عند النمو المبكر وعند بداية تكون البراعم، عند النمو المبكر وعند بداية تكوين الإزهار، وعند بداية تكون البراعم وعند بداية تكوين الإزهار. أستخدم الصنف هاي صن 33. خلال الموسميين. أوضحت الدراسة أن النتروجين له تأثير معنوي على طول النبات (سم) ودليل مساحة الورقة والوزن الجاف (جم) وعدد البذور/القرص ووزن الـ1000 بذرة (جم) ونسبة البذور الفارغة (%) وإنتاجية البذور ونسبة الزيت (%) في الموسمين. أوضحت النتائج  أن موعد إضافة النتروجين  للنبات له تأثير معنوي على طول النبات (سم) والوزن الجاف (جم) وعدد البذور/ القرص وإنتاجية البذور ونسبة الزيت (%) في الموسمين، بينما على وزن الـ 1000 بذرة ((جم) وإنتاجية البذور في الموسم الصيفي. تم الحصول على أعلى محصول من البذور (2852.4كجم /هكتار) عند المعاملة 86كحم/هكتار عند الفترة المبكرة وعند بداية الإزهار في الزراعة الصيفية             و(2373.6كجم/هكتار) عند المعاملة 129كحم/هكتار عند بداية تكوين البراعم وعند بداية الإزهار في الزراعة الشتوية. بينما أعطت المعاملة دون  إضافة و129 كجم نتروجين/هـ  أعلى نسبة زيت  في موسمي الصيف والشتاء على التوالي.  للحصول على أعلى إنتاج  بذور زهرة الشمس نوصي بإضافة 86 و129  كجم نتروجين/هكتار عند الفترة المبكرة وعند بداية الإزهار أو عند بداية تكوين البراعم وعند بداية الإزهار في الزراعة الصيفية والشتوية على التوالي. و للحصول على أعلى نسبة زيت  لا ينصح بإضافة النيتروجين تحت ظروف ولاية الجزيرة.